Keragaman Jenis dan Kelimpahan Populasi Penggerek Batang Padi dan Serangga Lain Berpotensi Hama Pada Ekosistem Sawah Organik - Hadi, Mochamad; Soesilohadi, RC Hidayat; Wagiman, FX; Soehardjono, Yayuk Rahayuningsih (Bioma : Berkala Ilmiah Biologi, 2013)
Rice stem borer is a main pest of paddy rice in Central Java. The main rice stem borer are yellow rice borer, Scirpophaga incertulas Walker, and white rice borer, S. innonata Walker. Other species are pink borer Sesamia inferens Walker, striped rice borer Chilo suppressalis Walker, dark-headed rice borer, C. polychrysus Meyrick, and glossy rice borer, C. auricilius Dudgeon. Besides rice stem borer, there are many other insect which are potential as rice pest, i.e., grasshopper, rice ear bug, brown planthopper, etc. Organic agriculture in Central Java have not been applied yet, hence there is still lack of information, including species diversity information and abundance of rice stem borer population and other potential insect pest on rice. Species diversity and population abundance of rice stem borer and other potential insect in organic rice ecosystem differ with the inorganic one. The objective of this research is to study species diversity and abundance of rice stem borer population and other potential pest in organic rice ecosystem. The study was conducted in organic rice of Bakalrejo Village, Susukan Sub district, District of Semarang. Species diversity and population abundance was analyzed using Shanon-Wiener’s species diversity index (H’), population abundance index (Di), and population evenness index (e). Pattern of  species diversity, population abundance, population evenness were temporally analyzed using population dynamic curve. Sampling of species diversity and population abundance was performed during a crop planting season with twice of sampling frequency. The result shows that rice stem borer found  were yellow rice borer with its population fluctuated temporally and pink rice borer with  its population were few and scarce. The highest diversity found during rice generative phase until ripen and decline in line with the age of rice. Species diversity index in vegetative phase was below 2, while during generative phase until ripen increased above 2. Insect population abundance declined in the end vegetative phase and increased in the beginning of reproductive phase until ripen phase. Population evenness index in all growth phase of rice were relatively high and similar. Keywords : organic rice, rice stem borer, insect pest of rice.